Fenomena Mandi Lumpur : Analisis Multidisiplin dan Relevansi Hadist Larangan Berbuat Zholim - Rizal; Risko Ari Saputra (PT. Hasba Edukasi Mandiri, 2026)
This study examines the phenomenon of the exploitation of vulnerable communities on digital platforms, specifically the practice of